Attitudes of primary school teachers towards teaching colloquialism (An exploratory study in the city of Ghardaia ) (مجلة الواحات للبحوث والدراسات, 2021)
This study aimed to identify the primary  school teachers’ attitudes towards demotic Arabic  teaching as well as to identify the differences according to sex and number of years of work and qualification . To achieve the objective of the study ,we  applied primary teachers’  questionnaire about demotic Arabic  teaching and make sure its  psychometric properties (honesty and fortitude) on a sample of 140 primary school teachers  of Ghardaia and using the descriptive exploratory and appropriate statistical methods and using statistical package for social sciences SPSS.19.0.It has come up with the following results:- There are negative trends among primary school teachers about teaching demotic Arabic. - There is no difference between the primary school teachers' attitudes towards teaching colloquially by sex.- There is a difference between the primary school teachers' attitudes towards teaching colloquially by the number of years of work.And because the topic is a virgin area and void from previous or preceding studies, we decided to deal with the topic with  the analysis of these results with the theoretical side all in illustrating the information we come up with  in the field. Keywords – Orientation, - Teachers, - Demotic Arabic language.